2018
DOI: 10.17116/oftalma201813405148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corneal refractive surgery on optical coherence tomography measurements

Abstract: В настоящее время кераторефракционные операции широко распространены в офтальмологической практике. Наиболее часто их выполняют у пациентов с миопией, в том числе высокой степени. У таких больных нередко имеет место сопутствующая патология глазного дна, требующая проведения высокотехнологичных диагностических исследований, в частности оптической когерентной томографии (ОКТ). Возникает вопрос, могут ли существенные изменения рефракции роговицы в результате ке

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Earlier, the authors showed in another study that a change in refractive power after laser-assisted in situ keratomileusis as large as 7.0 D produced minimal changes in average pRNFL of just 1 μm. 26 In conclusion, OCT instruments from most manufacturers do not consider the effect of refractive errors, especially of a high degree, on quantitative measurements of pRNFL. For the correct interpretation of the measurements of pRNFL in such patients, an original table was proposed, which provides a quick assessment of the results obtained on the Cirrus HD-OCT device.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier, the authors showed in another study that a change in refractive power after laser-assisted in situ keratomileusis as large as 7.0 D produced minimal changes in average pRNFL of just 1 μm. 26 In conclusion, OCT instruments from most manufacturers do not consider the effect of refractive errors, especially of a high degree, on quantitative measurements of pRNFL. For the correct interpretation of the measurements of pRNFL in such patients, an original table was proposed, which provides a quick assessment of the results obtained on the Cirrus HD-OCT device.…”
Section: Discussionmentioning
confidence: 98%
“…However, this difference could not influence pRNFL data. Earlier, the authors showed in another study that a change in refractive power after laser-assisted in situ keratomileusis as large as 7.0 D produced minimal changes in average pRNFL of just 1 μm 26 …”
Section: Discussionmentioning
confidence: 99%
“…In Table 5 of our manuscript, we discussed 7 papers that studied RNFL changes after refractive surgery. [4][5][6][7][8][9][10] We carefully reviewed them again, and we found that none of the 7 papers adjusted the axial length after refractive surgery. Furthermore, our findings are in agreement with those of 7 studies, which also did not find any significant changes in RNFL thickness after refractive surgery.…”
mentioning
confidence: 99%
“…Shpak AA et al found that in patients with very high myopia, a decrease of over 10 diopters (D) in corneal refractive power can increase the average thickness of the peripapillary retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer by 2 to 3 μm acquired by optical coherence tomography. 4 It is unclear whether this effect is mediated by magnification or by anatomical physiological change. However, in our cohort, there were no patients with such an extreme change in corneal refractive power, with an average spherical equivalent of À4.50 ± 1.77 D (range À8.00 to À1.75).…”
mentioning
confidence: 99%